PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN - Sri Uttari, Ida Ayu; Yadnya, I Putu (E-Jurnal Manajemen, 2018)
Firm value is an important indicator in assessing a company's performance. The size of a firm's value can affect investors in investing. Firm value can be affected by several factors such as liquidity, capital structure and dividend policy. The purpose of this study is to determine the significance of the influence of liquidity and capital structure to dividend policy and also to know the significance of the influence of liquidity, capital structure and dividend policy on firm value. This research was conducted at a manufacturing company listed in Indonesia Stock Exchange period 2013 - 2016. This study used by 21 companies by using purposive sampling method. This research uses path analysis technique (path analysis). Based on the analysis that has been done found that liquidity has a significant positive effect on dividend policy and firm value, while capital structure have a significant negative effect to dividend policy and firm value and dividend policy have positive significant effect to firm value.